Approach to Pediatric Lymphadenopathy - Chandran, Rabindran; Gedam, D Sharad (International Journal of Medical Research and Review, 2016)
Lymph node enlargement is common reason for outpatient department visit. A systematic approach is important to reach final diagnosis. It becomes further important because large numbers of patients are suffering from benign conditions.